Antibacterial Potential of Six Lichen Species against Enterococcus durans from Leather Industry Evaluation of acetone extracts obtained from several lichen species as alternative natural antibacterial agents - (:unkn) unknown (JOHNSON MATTHEY PUBL LTD CO, 2020)
Antibacterial resistant bacteria are a significant problem in the hide or skin soaking process due to their destructive properties on finished leather. Lichens may be a solution to overcome this resistance problem. Enterococcus durans (99.86%) was isolated from soak liquor samples. For screening of possible antibacterial effects of lichen acetone extracts, six lichen species (Hypogymnia tubulosa, H. physodes, Evernia divaricata, Pseudevernia furfuracea, Parmelia sulcata and Usnea sp.) were examined by nine-fold dilution against E. durans. H. tubulosa, H. physodes and E. divaricata extracts showed antibacterial effects at the concentrations of 240 mu g ml(-1), 120 mu g ml(-1) and 60 mu g ml(-1) whereas the extracts of P. furfuracea had an antibacterial effect at 240 mu g ml(-1) and 120 mu g ml(-1). On the other hand, P. sulcata had no antibacterial effect. The most successful lichen extract was determined to be Usnea sp. at the concentrations of 240 mu g ml(-1), 120 mu g ml(-1), 60 mu g ml(-1), 30 mu g ml(-1) and 15 mu g ml(-1). In conclusion, lichen extracts seem to have potential antibacterial efficacies against E. durans.
Keywords: ANTIMICROBIAL ACTIVITY; BACTERIAL-POPULATIONS; SALTED SHEEP; SOAK LIQUOR; CATTLE; HIDE; EXTERMINATION; QUALITY; SKINS